Evolutional law and elastoplastic constitutive model of structural loess considering moisture contents - Huanran Zhu; Weili Chen; Chenliang An; Haotian Zhang; Bing Han; Weixing Feng (PLoS ONE, 2026)
The deformation properties of natural undisturbed loess are intricately linked to its structural qualities. Structural characteristics can markedly improve soil stability, allowing structured loess to sustain a greater void ratio than disturbed loess under equivalent stress circumstances. This study examines the effect of initial moisture content on structural behavior by comparing the isotropic compression curves of disturbed and undisturbed loess under varying moisture conditions, thereby identifying the structural parameters of undisturbed loess and their changes during compression. A structural attenuation coefficient is developed to enhance the stress ratio-based structural parameter, and a quantitative approach for depicting structural degradation with axial strain is proposed, facilitating an effective evaluation of structural damage. Additionally, within the modified Cam–clay model framework, the yield surface equation is adjusted by integrating structural parameters, resulting in an elastoplastic constitutive model for structured loess that uniformly characterizes structural evolution under both spherical and shear stress. Finally, the suggested structural constitutive model is implemented in ABAQUS for numerical analysis, and comparisons with triaxial tests on undisturbed loess and published data confirm the model’s accuracy and applicability. The findings indicate that the established model accurately reflects the impact of initial moisture content on the structural strength, deformation properties, and degradation behavior of loess, offering a dependable theoretical foundation for the quantitative evaluation of loess structure and for engineering assessments in loess regions.